2019
DOI: 10.1111/cas.13908
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor effects of mAb against l‐type amino acid transporter 1 (LAT1) bound to human and monkey LAT1 with dual avidity modes

Abstract: l‐Type amino acid transporter 1 (LAT1) disulfide linked to CD98 heavy chain (hc) is highly expressed in most cancer cells, but weakly expressed in normal cells. In the present study, we developed novel anti‐LAT1 mAbs and showed internalization activity, inhibitory effects of amino acid uptake and cell growth and antibody‐dependent cellular cytotoxicity, as well as in vivo antitumor effects in athymic mice. Furthermore, we examined the reactivity of mAbs with LAT1 of Macaca fascicularis to evaluate possible sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Recently, Ueda et al tested whether targeting LAT1 by monoclonal anti-LAT1 antibodies might be a potential therapeutic approach. The authors found that the anti-LAT1 antibodies reduced proliferation of gastric and lung cancer cells in vitro and growth of colon cancer cells in vivo [81], suggesting that targeting LAT1 by monoclonal antibodies might be an alternative therapeutic option.…”
Section: Drug-mediated Inhibition Of Lat1mentioning
confidence: 99%
“…Recently, Ueda et al tested whether targeting LAT1 by monoclonal anti-LAT1 antibodies might be a potential therapeutic approach. The authors found that the anti-LAT1 antibodies reduced proliferation of gastric and lung cancer cells in vitro and growth of colon cancer cells in vivo [81], suggesting that targeting LAT1 by monoclonal antibodies might be an alternative therapeutic option.…”
Section: Drug-mediated Inhibition Of Lat1mentioning
confidence: 99%
“…We therefore, undertook the production of novel anti-HER3 mAbs. For the production of mAbs, in order to recognize the ECD of membrane proteins, we have so far utilized FCM to select mAbs reacting with transfectants expressing GFP-fused target molecules in a GFP-expression dependent manner as the first screening [27,28,41]. However, this method was difficult for rapid and simultaneous first screening of a large number of antibody samples.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted rat but not mouse species for immunizing animals to develop therapeutic anti-HER3 mAbs, since the total number of B lymphocytes in rats is several times larger than those in mice and the capacity to generate the antibody diversity in rats is superior to mice [27], and rat mAbs could be routinely humanized for antibody therapy as we reported previously [28]. In this study, we have successfully developed novel functional rat mAbs recognizing ECD of HER3 expressed on the surface of various human epithelial cancers, and analyzed the therapeutic potential of these mAbs, in addition to the analysis concerning their germline segments and complementarity-determining region (CDR).…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The avidity of mAbs against CRC cells was evaluated according to our previous report 16 . Briefly, cells were reacted with a range of mAb concentrations (100 ng ~ 30 μg/mL), followed by the incubation with PE‐conjugated secondary pAb.…”
Section: Methodsmentioning
confidence: 99%